Serological evidence of brucellosis in sheep and goats - KUMAR, PRAHLAD; SINGH, D K; BARBUDDHE, S B (The Indian Journal of Animal Sciences, 2013)
Serum samples of goats (289) and sheep (255) from Delhi abattoir were tested by Rose Bengal plate test (RBPT) , standard tube agglutination test (STAT), complement fixation test (CFT) and dot-enzyme linked Immuno-sorbent assay (dot-ELISA). In goats, the incidence was 1.73, 1.38,7.26 and 18.33%, respectively, on the basis ofRBPT, STAT, CFf and dot-ELISA, while in sheep, it was 9.00,4.31,27.48 and 10.58%, respectively, on the basis of RBPT, STAT. CFT and dot-ELISA The overall incidence of brucellosis among sheep was higher in Punjab (50.00%) as compared to sheep from Rajasthan (32.73%) whereas in goats, the incidence was highest in Rajasthan (29.71 %) followed by Uttar Pradesh (29.03%) and Punjab (15.83%). The study indicated that brucellosis is still a zoonotic problem in India.